Genome Wide Association Study (GWAS) of Chagas Cardiomyopathy in Trypanosoma cruzi Seropositive Subjects - Deng, Xutao; Sabino, Ester C.; Cunha-Neto, Edecio; Ribeiro, Antonio L.; Ianni, Barbara; Mady, Charles; Busch, Michael P.; Seielstad, Mark; Component, International (PloS one, 2013)
Familial aggregation of Chagas cardiac disease in T. cruzi-infected persons suggests that human genetic variation may be an important determinant of disease progression. To perform a GWAS using a well-characterized cohort to detect single nucleotide polymorphisms (SNPs) and genes associated with cardiac outcomes. A retrospective cohort study was developed by the NHLBI REDS-II program in Brazil. Samples were collected from 499 T. cruzi seropositive blood donors who had donated between 1996 and 2002, and 101 patients with clinically diagnosed Chagas cardiomyopathy. In 2008-2010, all subjects underwent a complete medical examination. After genotype calling, quality control filtering with exclusion of 20 cases, and imputation of 1,000 genomes variants; association analysis was performed for 7 cardiac and parasite related traits, adjusting for population stratification. The cohort showed a wide range of African, European, and modest Native American admixture proportions, consistent with the recent history of Brazil. No SNPs were found to be highly (P<10(-8)) associated with cardiomyopathy. The two mostly highly associated SNPs for cardiomyopathy (rs4149018 and rs12582717; P-values <10(-6)) are located on Chromosome 12p12.2 in the SLCO1B1 gene, a solute carrier family member. We identified 44 additional genic SNPs associated with six traits at P-value <10(-6): Ejection Fraction, PR, QRS, QT intervals, antibody levels by EIA, and parasitemia by PCR. This GWAS identified suggestive SNPs that may impact the risk of progression to cardiomyopathy. Although this Chagas cohort is the largest examined by GWAS to date, (580 subjects), moderate sample size may explain in part the limited number of significant SNP variants. Enlarging the current sample through expanded cohorts and meta-analyses, and targeted studies of candidate genes, will be required to confirm and extend the results reported here. Future studies should also include exposed seronegative controls to investigate genetic associations with susceptibility or resistance to T. cruzi infection and non-Chagas cardiomyopathy.